Animal Conceptual Metaphors in Kotowaza: A Cognitive Linguistic Study - Iffatu Masrura Al Hakimi (Universitas Muhammadiyah Yogyakarta, 2024)
The primary objective of this study is to examine the cognitive linguistic perspective of Japanese culture in relation to animal-related kotowaza. This study employs a qualitative descriptive approach to analyze 15 kotowaza from the comic book dictionary